Évaluation instrumentale du profil postural chez des handballeurs. Étude pilote à propos de 24 handballeurs - Ksibi, I.; Mrabet, A.; Mathlouthi, H.; Maaoui, R.; Bejaoui, A.; Rahali Khachlouf, H. (Science & Sports, 2016)
Introduction: The handball is a sport which requires static and dynamic control of the body balance. Objective evaluation of stabilometric parameters is interesting and allows improving functional parameters by postural rehabilitation according to the characteristics of sport activities. Objective: The objective of the study is to study the postural profile of the senior Tunisian handball players. Materials and methods: Cross-sectional study made in the department of physical and rehabilitation medicine in the Military Tunis hospital during January 2014, concerning senior handball players. All the subjects had a clinical and instrumental evaluation with static platform on two conditions: open eyes then closed eyes. The main postural parameters evaluated were the surface of the ellipse of confidence (S), the average position of the center of pressure following laterolateral and anteroposterior axis (x), the quotient of Romberg (QRBG), the length according to the surface (LAS) and the variance of the average speed of movement of center of pressure. We compared the main postural parameters to those measured in sedentary people. Results: Twenty-four handball players and 24 sedentary patients were included in the study. The main disturbed parameters were respectively the surface of ellipse of confidence (P = 0.04), the length according to the surface (P < 0.05), the quotient of Romberg (P = 0.04) and the variance of average speed of movement of the center of pressure, women being more stable than men in the two groups (P = 0.0001). Conclusion: Alteration of stabilometric parameters may be explained by the nature of sport evaluated, where the control of the body during movement is more important than the control of static posture, whereas our instrumental evaluation was on static and not on dynamic.